T Cell Dysfunction in Systemic Lupus Erythematosus - Gustin, Hanna; Raveinal; Dwitya Elvira (HM Publisher, 2024)
Systemic lupus erythematosus (SLE) is a systemic autoimmune inflammatory disease that can affect many organs in the body with very diverse clinical appearances. The prevalence of SLE in each country varies. The Lupus Foundation of America estimates that around 1.5 million cases occur in America and at least 5 million cases occur worldwide. The pathophysiology of SLE is very complex. The involvement of innate and adaptive immunity in the initiation and pathophysiology of SLE disease shows that there are interactions between leukocytes, cytokines, chemokines and tissue cells. T cells are the main component of the adaptive immune system which can kill infected host cells, activate other immune cells, produce cytokines and regulate immune responses. T cell dysfunction in SLE includes triggering inflammation through the secretion of pro-inflammatory cytokines, helping B cells produce autoantibodies and the accumulation of autoreactive T cells. Aberrations in T cells could be a therapeutic target for development and a potential SLE therapy.